Evaluation of Background Black Carbon Concentration in India - Maji Smaran; V. Vinoj (Aerosol and Air Quality Research)
Abstract Air pollution levels are rapidly increasing over the Indian region in recent times impacting the health and welfare of the general population of which black carbon (BC) is an important component. Significant efforts are being made to reduce pollution levels focusing on highly polluted cities. It is qualitatively known that a significant background BC pollution load exists over the Indian region. However, no systematic studies have focused on scientifically quantifying them. In this study, an effort is made to understand and segregate BC, an important primary aerosol/air pollutant, into the background (the minimum concentration levels that exist due to regional and long-range transport) and foreground concentrations (local emissions) using a simple methodology. The method is evaluated for consistency using ground-based observations (BC from Aethalometer) and extended to the whole Indian region using chemical reanalysis datasets (MERRA-2, Modern-Era Retrospective Analysis for Research and Applications, version 2). Our analysis reveals that the background BC over India reaches its highest during the winter season, 2.32 µg m–3 (background BC ~86%), and its lowest during the monsoon season, 0.60 µg m–3 (background BC ~79%). Furthermore, regardless of the season, the level of background BC in India exceeds 75% consistently. An independent evaluation of foreground BC after the removal of the background shows major emissions sources similar to the HTAP_v3 (Hemispheric Transport of Air Pollution) BC emission database, indicating the strength of the analysis. The high degree of qualitative agreement between foreground BC concentration and BC emission sources provides confidence in the analysis. These findings will provide policymakers with a valuable perspective, emphasizing the significant influence of background BC aerosol pollution in India.